Uji Aktivitas Antioksidan Ekstrak Metanol Tangkai Daun Strawberry (Fragaria x annanasa) Dengan Metode DPPH - Ayunda, Sarah; Etika, Sri Benti (Journal of Natural Sciences, 2024)
Free radicals are molecules that have one or more unpaired electrons in their outer orbit and are highly reactive. The severe reactions produced by highly reactive free radicals can produce unusual compounds and damage vital body cells. This study aims to determine the content of secondary metabolites and test the antioxidant activity of methanol extract of Strawberry  stem (Fragaria x annanasa). The Strawberry  stem samples used came from the Alahan Panjang area, West Sumatra. Extraction was carried out by maceration method using methanol solvent. The results of the maceration were then evaporated using a rotary evaporator to obtain a thick methanol extract of 13.3037 grams. Methanol thick extract was analyzed for secondary metabolite content by phytochemical screening. Antioxidant activity test using DPPH method. Methanol extract of Strawberry  petiole contains alkaloids, saponins and phenolics that have antioxidant activity that can counteract the formation of free radicals. The results of antioxidant tests conducted using UV-Vis spectrophotometry on methanol extract of Strawberry  petiole showed an IC50 value of 33.4816 ppm with a comparison using vitamin C as a positive control showing an IC50 value of 22.3024 ppm.